Therapists' characteristics associated with the (non-)use of exposure in the treatment of anxiety disorders in youth: A survey among Dutch-speaking mental health practitioners. (June 2020) - de Jong, Rachel; Lommen, Miriam J.J.; van Hout, Wiljo J.P.J.; de Jong, Peter J.; Nauta, Maaike H.
Abstract: Introduction: Although there is consensus that exposure is the key ingredient in treating childhood anxiety disorders, several studies in the USA suggest exposure to be underused in clinical practice. Previous research pointed to therapists' beliefs about exposure, their age, experience, caseload, training and theoretical orientation, as well as the level of the therapists' own anxiety as important factors in the underusage of exposure in the treatment of adult anxiety disorders. This study examined what therapist characteristics may be involved in the (non-)use of exposure in treating childhood anxiety disorders. Methods: An internet-based survey among 207 youth mental health care professionals in the Netherlands and Belgium was conducted to assess therapists' beliefs about exposure, their age, experience, caseload, training and theoretical orientation, as well as the level of the therapists' own anxiety, depression and stress. Results: The current survey showed that therapists used exposure in about half of their cases of childhood anxiety and that the non-use was independently associated with the relatively strong negative beliefs about exposure, therapists' age, and non-CBT orientation. Discussion: Findings point to the importance of addressing negative beliefs about exposure in therapists' training and supervision to resolve therapy drift away from exposure, and consequently improve utilization and delivery of exposure-based therapy for childhood anxiety disorders.